2005
DOI: 10.1128/iai.73.3.1475-1481.2005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vaccination of Calves against Hemorrhagic Septicemia with a Live aroA Derivative of Pasteurella multocida B:2 by Two Different Routes of Administration

Abstract: Two groups of four calves each were immunized either intramuscularly (i.m. vaccinated) or intranasally (i.n. vaccinated) at 2 and 6 weeks of age with ca. 10 9 CFU of a derivative of P. multocida serotype B:2 strain 85020 containing a deletion in the aroA gene (strain JRMT12). Both groups of calves and three unvaccinated control calves were challenged subcutaneously at 8 weeks of age with ca. 10 7 CFU of the wild-type 85020 strain. The first and second vaccinations caused a significant pyrexia and increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
2
24
1
Order By: Relevance
“…The apparent association of different mean IgM titers with groups preceded any differences in treatment and was coincidental. There was no significant increase in either serum IgG or IgM concentrations during the days following primary vaccination with any of the vaccine doses, in agreement with our previous work (12) and with the observations of others (4,13,20). If anti-P. multocida serogroup A:3 IgM antibody was present, it may have reacted with the vaccine dose, a phenomenon reported previously (2), thereby reducing the titer, as seen at day 14, and thus minimizing the humoral response to vaccination.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The apparent association of different mean IgM titers with groups preceded any differences in treatment and was coincidental. There was no significant increase in either serum IgG or IgM concentrations during the days following primary vaccination with any of the vaccine doses, in agreement with our previous work (12) and with the observations of others (4,13,20). If anti-P. multocida serogroup A:3 IgM antibody was present, it may have reacted with the vaccine dose, a phenomenon reported previously (2), thereby reducing the titer, as seen at day 14, and thus minimizing the humoral response to vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…with ca. 10 9 CFU of the P. multocida JRMT12 strain peaked at 24 h postvaccination and then declined (12), and a similar trend was also apparent in the present experiment after vaccination with 10 8 CFU. The low mean SAA concentrations and the lack of any significant differences in concentrations among the vaccinated groups after challenge suggest that vaccination with any of the three vaccine preparations was of similar efficacy in reducing the acute-phase protein response.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Boosmann et al (1989 have shown that bovine SAA, increases 100-fold in cattle inoculated experimentally with E. coli LPS toxins. Other experimental studies have measured the SAA response in cattle following inoculation of pathogens associated with BRD like M. haemolytica (Horadagoda et al, 1993), bovine respiratory syncytial virus (BRSV) (Heegaard et al, 2000) and P. multocida (Hodgson et al, 2005). Serum amyloid-A was observed to be a sensitive APP that reacts faster than Hp following infections (Alsemgeest et al, 1994 andHoradagoda et al, 1994).…”
Section: Serum Amyloid Amentioning
confidence: 99%